ASEPTICS ANTISEPTICS RULES - Khurramova Billura Otkir kizi (Scholar Express Journals, 2023)
Infection control is a critical aspect of healthcare, and it hinges on the principles of aseptics and antiseptics. Aseptics involve the prevention of infections through sterile techniques, while antiseptics are the agents used to inhibit the growth of microorganisms on living tissues. This article provides a comprehensive overview of aseptics and antiseptics, including their importance, methods of application, and their roles in healthcare. We also discuss the significance of proper infection control measures, as well as practical recommendations for healthcare professionals.
Keywords: Aseptics; antiseptics; infection control; sterilization